INFORMAL EDUCATION OF CATTLE BREEDER FAMILIES AT POJOK GIRANG KAMPONG CIKAHURIPAN VILLAGE - Siti Elah Julaeha; Lince Sari Dianawati Leatemia (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
The aim of this research is to explore the informal education process in cattle breeder families and to discover their point of view toward children education in Pojok Girang Kampong, Cikahuripan Village, the District of Lembang, the Regency of Bandung Barat. This qualitative descriptive research takes cattle breeder families as subjects taken by purposive sampling and snowball sampling techniques. Data is collected through observation, interview, and document study; and is analyzed through collection, presentation, reduction, and conclusion. The results show that: (1) the process of education in cattle breeder families mostly include parents educating and guiding their children especially regarding moral values, religion, economy, as well as the blessings of nature and personality development according to the children physical development stages, and (2) cattle breeder families view that education is of utmost important, yet a lot of factors influence in such a way they are constrained in their desire to provide their own kin education. Some others even described that education ‘is not so important’, merely limiting it to reading and writing.